Intelligent positioning of items in a tree map visualization - Leah, Robert; Parzygnat, Kenneth; Uthe, Robert (2008)
Displaying data from a data set in a tree map visualization is provided by prioritizing the data in the data set so as to associate a priority with respective elements of the data in the data set. A tree map visualization is generated based on the data set where a location of bounding boxes in the tree map is based on the priority associated with the corresponding element. Tree maps having locations of bounding boxes that are based on a priority associated with the bounding boxes are also provided.